Experimental analysis of polymorphic microsatellite loci in Cladocera: mixed breeding strategy and population dynamics - Poroshina A.A.; Sherbakov D.Yu. (Письма в Вавиловский журнал генетики и селекции)
The aim of this work is to identify polymorphic loci in Daphnia genomes using genome sequence analysis and experimental analysis of real accessions of samples collected in nature. We use primers predicted by an algorithm for DNA amplification from Daph- nia samples and capillary electrophoresis to detect polymorphic loci. This was done to detect polymorphic loci in a single experiment, when the presence of polymorphic loci with a frequency sufficient for genetic studies is detected as the appearance of multiple peaks on the electrophoregram. Thus, we evaluate the effectiveness of the capillary electrophoresis method and refine population para- meters, including the proportion of sexual reproduction and the effective population size. Studying polymorphic loci becomes es- pecially relevant in the context of climate change and anthropogenic impacts on ecosystems, as these factors can significantly affect genetic diversity and adaptation in populations. Polymorphic loci can serve as indicators of genetic stability and the ability of species to adapt to changing environmental conditions. In the face of global climate change and increasing anthropogenic impacts, such as pollution, urbanization, and landscape changes, populations face new challenges that require rapid adaptation. Polymorphic loci, due to their high variability, can provide valuable information about the genetic structure of populations and their potential for adapta- tion. In the context of our research, studying polymorphic loci in Daphnia becomes particularly important, given their ecological role and sensitivity to environmental changes. Daphnia, as key components of freshwater ecosystems, can serve as model organisms for studying genetic adaptation to climate change and anthropogenic impacts. Understanding polymorphic loci in Daphnia can provide valuable data for assessing genetic stability and adaptive potential in these populations, which is particularly important in the face of rapidly changing environmental conditions.